2018
DOI: 10.1111/ene.13583
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TREM2 in peripheral cells from mild cognitive impairment patients who progress into Alzheimer's disease

Abstract: These data seem to confirm the protective role of TREM2 in the pre-clinical stage of AD. Upregulation of TREM2 in MCI-AD could be a mechanism to counteract the activation of neuroinflammatory processes. It is possible that TREM2 and ApoE ε4 interact synergistically in the pre-clinical stage of AD. Therefore, TREM2 may be useful as an early peripheral biomarker for the development of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 36 publications
7
28
0
1
Order By: Relevance
“…Presently, the clinical relevance of an elevated serum sTREM2 level in AD is unknown [34]. Several studies have reported the sTREM2 level in the peripheral blood to be higher in AD patients than that in healthy individuals [47,48], whereas other investigators reported no significant difference [24,46]. This discrepancy may be attributed to the designation of groups, as important patient characteristics (i.e., gender, age, and disease stage) may affect the results.…”
Section: Localization Of Strem2mentioning
confidence: 98%
“…Presently, the clinical relevance of an elevated serum sTREM2 level in AD is unknown [34]. Several studies have reported the sTREM2 level in the peripheral blood to be higher in AD patients than that in healthy individuals [47,48], whereas other investigators reported no significant difference [24,46]. This discrepancy may be attributed to the designation of groups, as important patient characteristics (i.e., gender, age, and disease stage) may affect the results.…”
Section: Localization Of Strem2mentioning
confidence: 98%
“…AD-associated mutations lead to TREM2 dysfunction, so that microgliosis is compromised in such mutation-carrying patients and related AD model mice 31 , 32 . Both increased and decreased DNA methylation in the TREM2 gene have been reported 33 36 , though increased TREM2 expression has been consistently found in AD patients and mouse models and may be associated with the recruitment of microglia to amyloid plaques 37 . Moreover, TREM2 deficiency has been found to impair mTOR activation, increase autophagy, and cause metabolic dysfunctions in microglia 18 , 20 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…CSF YKL-40 levels negatively correlated with cortical thickness in specific AD-vulnerable areas, such as middle and inferior temporal areas in Aβ42-positive subjects [166] and grey matter volume in APOE ε4 carriers [167]. Interestingly, a positive association between CSF YKL-40 and t-tau has been reported in asymptomatic preclinical stages of AD and other NDDs [110,168], thus suggesting a link of YKL-40 with an underlying tau-driven neurodegenerative mechanisms [169].…”
Section: Biomarkers For Neuroinflammationmentioning
confidence: 97%
“…Unfortunately, plasma YKL-40 did not, so far, demonstrate utility as a diagnostic biomarker and for predicting cognitive decline (Table 2) [170,172]. To sum up, YKL-40 is an unspecific pathophysiological biomarker tracking immune/inflammatory response in NDDs, and it could be helpful as a monitoring biomarker for targeted anti-inflammatory therapies [169].…”
Section: Biomarkers For Neuroinflammationmentioning
confidence: 99%